Evaluation of Kartini V Street Canal Capacity using HEC-RAS - Imamuddin, Mohammad; Dewi, Firda Rachma (ASTONJADRO, 2025)
The Kartini V Street channel in Central Jakarta plays a vital role in directing the flow of water to the main channel on Kartini Raya Street through the Kartini Pump House, thus effectively addressing water pooling issues in the Kartini neighborhood area. Evaluation of the capacity of the Kartini V Street channel is carried out by comparing the planned rainfall discharge with the existing channel discharge. Hydrological analysis calculations for the planned discharge with a 5-year return period yield planned discharges of 0.0214 m3/second for channel A-B, 0.0068 m3/second for channel B-C, and 0.0226 m3/second for channel B-D. Meanwhile, calculations for the existing channel discharge result in 6.9756 m3/second for channel A-B, 9.3690 m3/second for channel B-C, and 12.0398 m3/second for channel B-D. The analysis indicates that the existing channel capacity is sufficient to accommodate the planned rainfall discharge.